Qualitative Research in International Settings: A practical Guide - Stephens, David (Routledge, 2009)
The teaching of qualitative research skills in universities is now widespread and the number of institutions offering courses in research methods in education and the social sciences is growing, while professionals in the fields of education, health and the social services are increasingly required to carry out research, evaluation and reviews.
Keywords: formation des adultes; utilisation des recherches